Implementasi Learning Management System sebagai Inovasi Pembelajaran di Era Digital pada PT. Surya Pratista Hutama (Jurnal Pelayanan Masyarakat, 2025)
PT. Surya Pratista Hutama, as a company committed to improving the quality of its human resources, continues to strive to provide innovations to support employee competency development. One strategic step taken is the implementation of a Learning Management System LMS as a form of learning innovation in the digital era. This LMS implementation is not only intended as a means of knowledge transfer, but also as a medium to create a culture of sustainable learning within the company environment. The observation conducted aims to determine the extent to which the LMS can support the learning process in the company, with a focus on its effectiveness, challenges, and impact on improving employee competency. The method used is a descriptive study with a qualitative approach, through interviews, direct observation, and documentation related to digital-based learning activities. The observation results show that the implementation of the LMS provides various benefits, including easy access to learning anytime and anywhere, flexibility that allows employees to adjust their learning schedules to work activities, and increased motivation and independence in learning. However, there are several obstacles that require attention, such as limited digital literacy among some users, lack of direct interaction between instructors and participants, and the need to adjust content to be more relevant to daily work demands. Overall, the LMS has great potential to improve the effectiveness of training at PT. Surya Pratista Hutama.